To Be Named Something Else - Phenix, Shaina (Book collections on Project MUSE., 2023)
"To Be Named Something Else, winner of the 2023 Miller Williams Poetry Prize, is a high-spirited celebration of Black matriarchy and lineage-both familial and literary. Centering the coming-of-age of Black femmes in Harlem, Shaina Phenix's debut collection, in the words of series judge Patricia Smith, "enlivens the everyday-the everyday miraculous, the everyday hallelujah, the numbing everyday love, the everyday risk of just being Black and living.""--